The complexity of determining the existence of genocidal intent - Sadmir Karović (Zbornik Radova Pravnog Fakulteta u Splitu, 2014)
The author emphasized the complexity of determining the existence of genocidal intent as specific characteristics of the crime of genocide. The practice of international justice is significantly enabled a clearer, simpler and more precise understanding of the definition of the subjective component of the crime in determining individual criminal responsibility. The burden of proving the crime of genocide specifically refers to the inability to define the direct genocidal intent. Indirect evidence in itself is complex and requires a number of indirect factors pointing to the only reasonable conclusion in the context of the existence of genocidal intent of the perpetrator of the crime. Aggravating circumstance that affects the complexity of determining the existence of genocidal intent is the generality of the Genocide Convention, which is prescribed by clear criteria and standards for determining the quantitative component of the crime.